Diversity of weeds in organic and conventional paddy field / Muhammad Hafiz Pauzan - Pauzan, Muhammad Hafiz (Faculty of Plantation and Agrotechnology, 2015)
Weed is unwanted plants that grow at unwanted place. In paddy field, this plant will compete with the crop to get nutrient, space, water and light. This competition will cause lowering paddy yield and reduce the quality and paddy grade. In order to study the diversity of weed species and comparing the population between organic and conventional paddy field, the weeds found in the field was collected. The weeds was identified and documented as a herbarium. The level of species similarities was determine using Jaccard Similarity Coefficient in Multi Variate Statistical Programme. This research shows that there are 11 weed species found in organic paddy field and 2 weed species found in conventional paddy field comprising of 7 annuals and 4 parennials. The similarity level between these organic and conventional paddy field was low which is 18.18%. The factor that contribute to this result also stated to considered as future improvement of the study to be conducted in the future.